Islamic vs. Conventional Banks in Syria: Analysis on Financial Performances - Khaled Nour Aldeen; Sri Herianingrum; Ziad Mhmmad Wafik al Agawany (Shirkah: Journal of Economics and Business, 2020)
Doubtful finance is the worst nightmare for banks, but this can be avoided if a bank follows a proper strategy to avoid such kind of finance. Due to the violent political crisis in the country, most of the contemporary studies have excluded Syria from their samples. The present study aims to evaluate the performances of Islamic and conventional banks in Syria through a comparative analysis. A secondary aim of this study is to shed some light on the main factors influencing non-performing finance in both Islamic and conventional banks. This study addressed the entire private banking sector in Syria consisting of 11 conventional banks and 3 full-fledged Islamic banks over the period of 2011-2017. To this end, several financial ratios and macroeconomic variables along with independent sample t-test and panel data regression were employed. The results indicated that the Islamic banks were better in terms of assets quality. Panel data regression manifested that gross domestic product growth, exchange rate, finance to deposit ratio, and operating expenses ratio had a significant impact on non-performing finance. This study provides an alluded picture of Syrian private banking sectors that enables authorities to deliberate on the pertinent macroeconomic NPF determinants such as exchange rate and GDP growth.